Implementasi Elemen User Interactive (UI) Dan User Experience (UI) Dalam Perancangan Antarmuka Sistem Informasi E-Tourism Di Bali Berbasis Web - Aulia Iefan Datya (LPPM Universitas Dhyana Pura, 2019)
ABSTRACTUser Interface (UI) and User Experience (UX) are two crucial factors in the success of information systems, especially web-based applications and mobile applications. Design elements in web or mobile applications can be made more atrractive, by applying several elements in human-computer interaction theory based on user segmentation, product knowledge, consumer behavior, latest marketing theories, both in terms of visuals, after-effects, display sets, content, multimedia, lay-out menus on the web or mobile applications. In the recent state development of tourism in Bali, tourism transactions and promotions are already based on E-Tourism using web media and mobile applications. Making it easier for tourists to access information and services related to ticketing, transportation, accommodation and even travel packages. This study uses the User Interface (UI) and User Experience (UX) methods to view usability and web-quality from a web-based E-Tourism websites that promotes tourism in Bali.Keywords: User Interface, User Experience, E-Tourism, Informastion System, Bali Tourism.ABSTRAKUser Interface (UI) dan User Experience (UX) adalah dua faktor krusial dalam keberhasilan sistem informasi, terutama aplikasi berbasis web dan aplikasi mobile. Elemen desain dalam web dapat dibuat lebih menarik, dengan menerapkan beberapa elemen dalam teori interaksi manusia-komputer berdasarkan segmentasi user, pengetahuan produk, perilaku konsumen, teori pemasaran terbaru, baik dari segi visual, after-effect, display set, konten, multimedia, lay-out menu di web atau aplikasi mobile. Dalam perkembangan pariwisata di Bali saat ini, transaksi dan promosi pariwisata sudah berbasis E-Tourism dengan menggunakan media web dan aplikasi mobile. Sehingga mempermudah wisatawan dalam mengakses informasi dan layanan terkait dengan ticketing, transportasi, akomodasi bahkan paket perjalanan wisata. Penelitian ini menggunakan metode User Interface (UI) dan User Experience (UX) untuk melihat usability dan web-quality dari website layanan E-Tourism yang berbasis web yangmempromosikan pariwisata di Bali.Kata kunci: User Interface, User Experience, E-Tourism, Sistem Informasi, Pariwisata Bali.